TAYAMMUM DALAM QS. AL-NISA' AYAT 43 : Pendekatan Tafsir Muqāran - Maimoen, Abdul Ghofur; Alfi, Ahmad Musonnif (AL ITQAN: Jurnal Studi Al-Qur'an, 2021)
This study examines the interpretation of QS. al-Nisa`: 43 which discusses tayammum. The significance of this research is that in understanding QS. al-Nisa`: 43, there are many differences of opinion among scholars about the meaning and procedure of tayammum. Therefore, this article is presented by using qualitative methods and muqāran interpretation as an approach. Tayammum hadith facts and their context will also be presented to understand the QS. al-Nisa`: 43 comprehensively. This study shows that there are at least four points of difference among scholars regarding the interpretation of the words mardhā, safar, Falam Tajidū Māan, and ṣa‘īd. Such differences are caused by some scholars who do not consider the hadiths of tayammum comprehensively.